Offloading Optimization for Energy-Minimization Secure UAV-Edge-Computing Systems - Gu, Xiaohui; Zhang, Guoan; Gu, Jinyuan (IEEE Wireless Communications and Networking Conference : [proceedings] : WCNC, 2021)
This paper considers a mobile edge computing (MEC) system where an unmanned aerial vehicle (UAV) offloads demanding computational tasks to the access point (AP), and AP cooperatively sends jamming noise to protect the confidentiality and secrecy of data transmission. In this system, the computation from UAV is portioned into two parts with one executed locally on UAV and the other offloaded to MEC for processing. To minimize the total energy-consumption of UAV for computing and offloading, we jointly optimize computation and communication resource allocation, subject to secure offloading rate and computation-latency constraints. Although the formulated problem is non-convex, we transform it into a convex problem by analytical means. Numerical results verify the superiority of our proposed scheme in terms of energy-consumption and quantify the performance of our proposed offloading scheme in various scenarios.